A Polymer Film Dye Laser with Spatially Modulated Emission Controlled by Transversely Distributed Pumping. (27th September 2016) - Wardosanidze, Zurab V.; Chanishvili, Andro; Chilaya, Guram
Abstract : Spatial modulation of laser emission controlled by the structure of excitation light field was demonstrated. A dye doped polymer film as an active medium was sandwiched between two laser mirrors forming a laser cell. The pumping was performed by an interference pattern formed with two mutually coherent beams of the second harmonic of a Q-switched Nd:YAG laser (532 nm) and located in the plane of the laser cell. The laser emission was observed normally on the plane of the cell. The cross section of the obtained laser emission was modulated in intensity with an interval between maximums depending on the period of the pumping interference pattern. Thus, the emitted light field qualitatively looks like diffraction from an elementary dynamic hologram, that is, a holographic diffraction grating.